Inventory control system using threshold method for automotive industry - Arya Fadillah; Bayu Priyatna; Fitria Nurapriani; Tukino Tukino (Institute of Computer Science (IOCS), 2026)
Inventory control is a critical aspect in manufacturing companies to ensure the availability of materials and support smooth production processes. Ineffective inventory management can lead to stock shortages or overstock conditions, which may disrupt operational activities. This study aims to develop a web-based inventory control system using the Reorder Point (ROP) method to optimize stock management in a manufacturing environment. The system is designed to monitor stock levels, calculate Average Daily Usage (ADU), safety stock, and reorder points automatically. When stock reaches a predefined threshold, the system provides notifications to assist decision-making in replenishment processes. The development method used in this study is the Waterfall model, including analysis, design, implementation, and testing stages. The system is implemented using the CodeIgniter framework and MySQL database. Testing results show that the system can accurately calculate ROP values and effectively provide early warnings for low stock conditions. Therefore, the proposed system can improve efficiency, reduce the risk of stock shortages, and support better inventory management in manufacturing companies. The system achieved an accuracy rate of 100% in calculating ROP values based on Black Box testing results, and successfully generated real-time notifications for all critical stock conditions. The novelty of this study lies in the integration of threshold-based logic with automated notification features in a web-based system, which provides a more responsive and practical solution compared to previous inventory control approaches that rely on manual monitoring.